Pengaruh E-Commerce dan Integrasi Teknologi terhadap Keberlanjutan UMKM Pascabencana melalui Nilai Pelanggan Unggul - Al Mahfud Saputra; M Rasyidin; Yusrawati Yusrawati; Azka Rizkina (Forum Kerjasama Pendidikan Tinggi, 2026)
This study examines the effects of e-commerce adoption and technology integration capability on the sustainability of micro, small, and medium enterprises (MSMEs), with superior customer value serving as a mediating variable in a post-disaster context. The main issue addressed is the suboptimal use of digital technology by MSMEs in sustaining business operations following disasters, which often cause operational disruptions, declining demand, and limited market access. This study employed a quantitative explanatory approach involving 200 MSME owners, selected using purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The novelty of this study lies in examining the mediating role of superior customer value in explaining the relationship between digital transformation and MSME sustainability under crisis conditions. The results indicate that e-commerce adoption significantly affects superior customer value (β = 0.384; p < 0.001) but has no direct effect on MSME sustainability (β = 0.039; p = 0.492). Technology integration capability significantly affects both superior customer value (β = 0.446; p < 0.001) and MSME sustainability (β = 0.148; p = 0.013). Superior customer value also has a significant positive effect on MSME sustainability (β = 0.644; p < 0.001). The model explains 50.1% of the variance in superior customer value and 59.1% of the variance in MSME sustainability. These findings suggest that post-disaster MSME sustainability depends more on the ability to create customer value than on technology adoption alone.